Pemikiran Taha Husain - Barsihannor Annur (Universitas Islam Negeri Alauddin, 2014)
Taha Husain was an intellectuals figure who was very controversial with his ideas. He disclosed some reform idea that was considered “strange” and irrasional. According to him, to advance the moslem world, secularizing the education and religion must be implemented. The old Egypt and modern West must become role model how to develop moslem world. Religion could not be mixed with politic. religion must be separated from politic. To be the enlightened nation, the people who live in the country must be educated with standardized education. According to Taha Husain, Western education was a good model of education which can be implemented.